Effect of biological control in nematode Meloidogyne Spp in lulo (Solanum quitoense Lam) - Salazar G., Claudia; Betancourth G., Carlos; Castillo M., Alvaro (Revista de Ciencias Agrícolas, 2013)
Quito orange (Solanum quitoense L.) cultivation in Colombia shows production limiting diseases, caused by root knot nematodes Meloidogyne sp. that slowly destroys plantations, causing around 50% of losses. The situation in Nariño is the same; there for it his study was carried out in order to evaluate the biocontrol effect of fungal on the pathogen. 36 treatments were compared in greenhouse corresponding to Beauveria bassina, Metarhizium anisopliae and Paecilomyces lilacinus at concentration of 1x106 to 1x109and three application rates of 20cc, 30cc and 40cc, plus an absolute control, with five repetitions and an experimental unit of 10 plants. At two months of age, plants were inoculated with each drench treatment and ten days after, 10000 eggs of Meloidogyne spp were applied at the root base in a solution of 50cc.the evaluated variables were: incidence and severity, determining as a selection criteria treatments that showed less than 2 of severity and less than 30% of incidence. In field, a randomized block design with six treatments and three replications was carried out. The variables evaluated were incidence, severity and yield. The variance analysis and comparison test indicated that treatments Paecilomyces sp. at a concentration of 1x106and a dose of 30 cc and the chemical (carbofuran), showed the lowest severity levels (<1) and the highest average yield per hectare. It can be conclude that the biological control with the fungus Paecilomyces sp. is an alternative to the integrated management of root knot nematode.